2014
DOI: 10.1021/am5042548
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing Controllable Footprint Lines by Regulating the Dynamic Wettability of Coalescing Ink Droplets

Abstract: Inkjet printing lines with controllable footprints is the prerequisite of fabricating high-quality patterns. However, achieving precise footprints of lines by inkjet printing is still a challenge because of the difficulty in controlling coalescences of ink droplets. Here, controllable footprint lines were fabricated by adjusting the ink droplets' dynamic wettability which is depended on the ink droplets' surface tension difference. The experimental surface tension difference of 0.77-1.50 mN/m leads to appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 26 publications
0
68
0
2
Order By: Relevance
“…These colored patterns can be designed as desired by computer software programs. Furthermore, by controlling the coalescences of the colloidal latex ink droplets, Liu et al (2014) achieved high-quality patterns of photonic crystal lines, as demonstrated in Figure 5.1(d). Besides large-area flat-panel display, the printed photonic crystals can also be applied for the wide viewing-angle displays by patterning them into the dome-like structures, as shown in Figure 5.1(b).…”
Section: Monodispersed Polymer Nanoparticle Latexesmentioning
confidence: 95%
See 2 more Smart Citations
“…These colored patterns can be designed as desired by computer software programs. Furthermore, by controlling the coalescences of the colloidal latex ink droplets, Liu et al (2014) achieved high-quality patterns of photonic crystal lines, as demonstrated in Figure 5.1(d). Besides large-area flat-panel display, the printed photonic crystals can also be applied for the wide viewing-angle displays by patterning them into the dome-like structures, as shown in Figure 5.1(b).…”
Section: Monodispersed Polymer Nanoparticle Latexesmentioning
confidence: 95%
“…As shown in Figure 5.1, monodispersed polymer microsphere latex inks are printed to fabricate photonic crystal patterns for the purpose of color displaying (Cui et al, 2009;Liu et al, 2014;Park et al, 2006). Figure 5.1(a) demonstrates that large-area patterned photonic crystals with multi-stopbands are fabricated by taking advantage of a commercial inkjet printer (Cui et al, 2009).…”
Section: Monodispersed Polymer Nanoparticle Latexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inkjet printing has been recognized as one of the most promising methods to fabricate patterns on various substrates [28,29,30,31,32,33,34,35]. However, it is still a challenge to inkjet print controllable patterns on a low-adhesive PDMS surface [36,37,38], because the coalesced inkjet droplets tend to become a larger droplet due to the sliding three phase contact line with a driving force of shape relaxation [39,40,41,42]. In the traditional method, there would need to be some modifications to the PDMS surface before inkjet printing, such as oxygen plasma treatment or grafting polymer [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…18 Technical applications of droplet coalescence include inkjet-printing, 9,10 surface cleaning, 11 coating, 12,13 and microuidic devices. 14 Investigating the mechanism of spreading a liquid drop on a liquid subphase is also relevant for medical applications such as transporting drugs through the lungs tissue.…”
Section: Introductionmentioning
confidence: 99%